Corporate electoral donations and tax aggressiveness - Antonio Lopo Martinez; Hettore Sias Telles; Viviane Chiachio (RAUSP Management Journal, 2020)
Purpose – The purpose of this paper is to investigate whether companies that donate to winning electoral campaigns are more aggressive in terms of tax planning than companies that do not make these contributions. The relationship between politicians and companies may be signaled by political connections in which companies try to get political benefits in exchange for providing politicians with campaign financing. The hypothesis is that a quid pro quo occurs in which these companies benefit from favorable tax treatment that reduces their relative tax burden. Design/methodology/approach – The focus of this study is donations that were made in the presidential elections of 2010 and 2014. The sample covers the period between 2010 and 2016 for companies listed on the B3 Stock Exchange, using proxies for tax aggressiveness computed based on value-added reporting. Through linear regressions, the authors have tested whether the companies that made these campaign contributions tend to have a lower tax burden. Findings – The proposed hypothesis was confirmed, revealing that a political connection between campaign donations reduces the tax burden for donating companies during the years following the election. These donations appear to depict an environment characterized by an exchange of favors in which the donating companies exhibit greater tax aggressiveness than non-donating companies. Originality/value – The current study deals with a subject that has not yet been examined empirically in Brazil and reinforces the position adopted by the Supreme Court in prohibiting campaign donations to inhibit quid pro quo practices. The study offers additional arguments for the criminalization of the so-called “second set of books” used to record electoral campaign contributions.